Effect of the Inoculation Site of Bovine and Avian Purified Protein Derivatives (PPDs) on the Performance of the Intradermal Tuberculin Test in Goats From Tuberculosis-Free and Infected Herds - Ortega, Javier; Roy, Álvaro; Álvarez, Julio; Sánchez-Cesteros, José; Romero, Beatriz; Infantes-Lorenzo, Jose A.; Sáez, José L.; López, Marisol; Domínguez, Lucas; de Juan, Lucia; Bezos, Javier (Frontiers in Veterinary Science, 2021)
The single and comparative intradermal tuberculin (SIT and CIT) tests are used for the ante-mortem diagnosis of caprine tuberculosis (TB). The tuberculin injection site has been associated with a different performance of the test in cattle. In contrast to that required in cattle in Europe (cervical injection), it can be carried out in the scapular region in goats. Nevertheless, there are no previous data concerning the effect of the injection site on the performance of the test in goats. The aim of the present study was to evaluate the effect of two different inoculation sites (cervical and scapular) on the performance of the SIT/CIT tests. This was done by intradermally inoculating 309 goats from two infected herds and one TB-free herd with both avian and bovine PPDs in the mid-cervical and scapular regions. None of the animals from the TB-free herd had positive reactions, and the number of reactors was not significantly higher, regardless of the inoculation site, in the high and low prevalence herds. However, significantly higher increases in skin fold thickness were observed on the cervical site when compared to the scapular site after the avian and bovine PPD inoculations in the TB-free herd (p < 0.001) and after the bovine PPD injection in the high prevalence herd (p=0.003). The presence of clinical signs was also more evident on the cervical site when using avian and bovine PPDs in the high prevalence herd (p < 0.01). In contrast, increases in higher skin fold thickness were observed on the scapular site when compared to the cervical site after the bovine and avian PPD inoculations were employed in the low prevalence herd (p<0.01). These results suggest that the cervical injection of PPDs may improve the sensitivity of the intradermal tuberculin test in high TB prevalence caprine herds, mainly owing to the increased presence of local clinical signs and a better performance of the CIT test. Moreover, specificity was not affected when using standard interpretations although further analyses in a great number of herds are required in order to confirm these findings.